Ramadhan and the quran - Khan, Saniyasnain (Goodwork Books New Delhi, 2005)
Ramadhan and the Quran by Saniyasnain Khan explores the deep connection between the holy month of Ramadan and the Quran, emphasizing the importance of reciting and reflecting on the Quran during this sacred time. Through engaging storytelling, it teaches young readers about the spiritual benefits of fasting and the guidance found in the Quran.